Morphological development of Sulaimani, from its establishment to today's globalization era - Hussein, Shakhawan Abdullah Hussein; Al-Butani, Prof.Dr.Talaat Tahir Mohammed Al-Butani; Palani, Prof.Dr.Ibrahim Qasim Palani (Sulaimani Journal for Humanities, 2026)
The study provides a historical analysis of the development of the morphological characteristics of Sulaimani between 1784-2024, ie from the era of regionalization to the era of globalization of the city and its opening to the world. It attempts to answer the question of how political, economic and social forces have shaped the shape and size of the city throughout history. The study divides the development of the city into four main morphological stages. The first period (1784-1947) was a slow and organic growth within the strength of the city's own local influences, in which constant political instability prevented the city from expanding. The second period (1948-1977) saw the first major leap in the expansion of Sulaimani, where state development projects and the drafting of the first master plan played a role in this development It has changed an organized and geometric style. The third period (1978-2002) is the period of explosive growth, which was the result of two opposing forces: forced urbanization under the policies of the previous regime, and the city becoming a major political center after the 1991 uprising. The fourth phase (2003-2024), the phase of globalization and economic opening, is considered the most important and influential phase. During this period, Sulaimani has undergone a huge horizontal expansion, increasing its area almost fivefold. The main findings of the study show that there was a fundamental change in land use patterns during this period, with the proportion of land for residential purposes decreasing significantly, while the proportion of commercial and service uses increased significantly. Each stage has left its own mark on the physical appearance of the city, but the globalization stage has been the strongest factor in shaping the contemporary appearance of the city, so that the morphology of a local city has passed and globalization has given it a new global appearance.
Keywords: Urban Morphology; Sulaymaniyah; Regionalism; Globalization